Population Pharmacokinetics and Exposure‐Response Analyses of Savolitinib Alone or in Combination With Osimertinib in Patients With Locally Advanced or Metastatic Solid Tumors - Azar Shahraz; Thibaud Derippe; Kiran Kumar Kode; Jessica Allmond; Simon Nelson; Ike Igwegbe; Aarti Sawant‐Basak; Karthick Vishwanathan; Kowser Miah (Clinical and Translational Science, 2026)
ABSTRACT Savolitinib (ORPATHYS) is an oral, highly selective inhibitor of the mesenchymal–epithelial transition (MET) receptor tyrosine kinase that has demonstrated clinical activity across multiple advanced solid tumors. A comprehensive population pharmacokinetics analysis using cumulative data from 998 patients across 10 clinical studies characterized savolitinib pharmacokinetics, its variability, and the impact of intrinsic and extrinsic factors. In a covariate search, no retained covariates had a clinically meaningful impact on steady‐state exposure of savolitinib. Model‐predicted savolitinib exposures were used to evaluate the relationship between savolitinib exposure and efficacy endpoints in the SAVANNAH Phase II study (NCT03778229; N = 360), in subpopulations defined by MET biomarker status. Among patients treated with savolitinib 300 mg once daily, 600 mg once daily, or 300 mg twice daily with osimertinib 80 mg once daily in SAVANNAH, a positive trend was observed between the trough concentration (Cmin,ss) at steady state and the objective response rate in all‐comer population, whereas no clear trend was observed in patients with high MET biomarker status, defined as MET immunohistochemistry (IHC) 3+/≥ 90% and/or fluorescence in situ hybridization (FISH) 10+. These findings support Cmin,ss as the exposure metric most informative for maintaining MET target coverage and for guiding a trough‐driven dosing strategy. Exposure–safety relationships were assessed across all 10 studies and no statistically significant associations were identified between savolitinib exposure and the occurrence of most safety events. These integrated population pharmacokinetics and exposure–response findings provide supportive evidence relevant to dose evaluation and clinical development of savolitinib in combination with osimertinib.